Sosialisasi Pemanfaatan Tandan Kosong Kelapa Sawit pada Tanaman Jagung di Pesantren: The Socialization of Utilizing Empty Palm Oil Fruit Bunches on Maize in Islamic Boarding Schools - Mardhiana, Mardhiana; Meilissa, Bethy; Adiwena, Muh. (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Islamic Miftahul Ulum Boarding Schools in Tarakan City, North Kalimantan, implements sustainable agricultural methods by utilizing empty fruit bunches (EFB) as organic fertilizer to enhance corn productivity. Through outreach activities, field demonstrations, and educational material distribution, students are taught how to process EFB and its application in corn cultivation. This approach not only reduces dependence on chemical fertilizers but also supports food security and maintains environmental balance. The results indicate an improvement in students' understanding and skills in environmentally friendly agricultural practices.